2019
DOI: 10.1080/10130950.2019.1677162
|View full text |Cite
|
Sign up to set email alerts
|

Trading firms and the gender wage gap: evidence from South Africa

Abstract: Firms engaged in international trade account for a large share of South Africa's output and employment. Therefore, their behaviour has potentially large effects on national outcomes including gender inequality. In this paper, we test whether the gender wage gap (GWG) of trading firms differs from that of domestic firms based on a growing literature that has outlined how the special characteristics of trading firms could lead to such a different GWG. Using a unique employer-employee matched data panel from 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Indeed, Ebrahim and Lilenstein (2019: 16) call for such research to evaluate 'the extent to which trade can create opportunities or improve employment for women', especially as a gender variable has subsequently been included in updated versions of the South African Revenue Services (SARS) administrative data. As such, we provide, in a previous preliminary study, evidence that both men and women in trading firms earn more than their counterparts in non-trading firms, but that the GWG is greater for trading firms (Bezuidenhout et al 2019). Considering this, in the sections below we further explore the differential GWG of traders and the channel(s) behind it.…”
Section: Literature Overviewmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, Ebrahim and Lilenstein (2019: 16) call for such research to evaluate 'the extent to which trade can create opportunities or improve employment for women', especially as a gender variable has subsequently been included in updated versions of the South African Revenue Services (SARS) administrative data. As such, we provide, in a previous preliminary study, evidence that both men and women in trading firms earn more than their counterparts in non-trading firms, but that the GWG is greater for trading firms (Bezuidenhout et al 2019). Considering this, in the sections below we further explore the differential GWG of traders and the channel(s) behind it.…”
Section: Literature Overviewmentioning
confidence: 74%
“…This is an interesting observation but does not provide us with any insights as to what could be contributing to the trend or whether it could be considered causal. A link between the GWG and the trading status of firms in South Africa has been already established by Bezuidenhout et al (2019), but only the rigorous empirical approach described in the previous section allows us to identify a causal effect. Finally, Figure 3 presents the share of female employment in manufacturing firms for each income quintile of the employees, disaggregated by trading status.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…For example, Mosomi (2019) finds that the gender wage gap remained at an average of 23% and 25%. According to Bezuidenhout et al (2019) the gender wage gap also depends on the status of a firm. For example, the authors used a unique employee-employer matched data panel from 2011 to 2016 for South Africa and employing fixed effects regressions found that the gender wage gap of trading firms was higher than domestic firms.…”
Section: Economic Inequalitymentioning
confidence: 99%
“…Another channel relates to the requirements of exporters and importers. As these firms typically require more flexibility with respect to work hours and business travel, they prefer male employees (Bøler et al, 2018;Bezuidenhout et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We analyse the role of trading firms for gender equality in South African manufacturing in two complementary studies(Bezuidenhout et al, 2019 and Janse van Rensburg et al, 2020).…”
mentioning
confidence: 99%